Beyond the emergency: Centering mental health in community disaster preparedness and recovery - Omolola E. Adepoju; Ashley M. Smith; Laura A. de la Roche; David Curtis (PLoS ONE, 2026)
Background Extreme weather events are increasing in frequency and severity, disproportionately affecting marginalized and under‑resourced communities. In Houston, Texas, where insurance coverage and mental health access remain limited, successive disasters compound existing inequities, leaving residents with unmet psychological needs. Yet little is known about how chronically impacted communities conceptualize their mental health experiences, barriers to accessing care, and priorities for support following repeated disaster events. Methods We conducted a qualitative study using town hall–style community conversations in three historically underserved Houston communities (Kashmere Gardens, Third Ward, Fifth Ward). A total of 145 residents participated between March and October 2024. Discussions followed a semi‑structured guide and were captured through trained note‑takers using a standardized template, supplemented by graphic recording. Reflexive thematic analysis, employing an inductive approach and an audit‑trailed consensus process, was used to identify themes. Researcher triangulation, persistent observation, and reflexivity were used to enhance trustworthiness. Results Three themes emerged. (1) Living in “survival mode”: residents described cumulative emotional exhaustion driven by repeated disasters, including persistent anxiety, hypervigilance, grief, caregiving burdens, and limited capacity for self‑care. (2) Navigating stigma, mistrust, and limited access: participants highlighted cultural stigma, confusing and costly pathways to care, and mistrust stemming from unfulfilled institutional promises and inaccessible services. (3) Building a path forward: residents emphasized the need for mental health literacy, community‑embedded services, improved communication with city officials, and sustained funding for affordable, accessible, and culturally responsive mental health support. Conclusions Successive disasters create chronic psychological strain in high‑vulnerability communities while simultaneously limiting access to care. Findings underscore the need for disaster mental health strategies that move beyond the acute response period to include community‑embedded supports, continuity of care, and investments in mental health literacy and affordability. Centering community voices is critical for developing equitable, sustainable, and culturally attuned disaster mental health systems.